Effects of Thawing on Frozen Semen Quality of Limousin and Brahman Bulls - Pratiwi, WC; Affandhy, L; Ratnawati, D (ANIMAL PRODUCTION, 2009)
The success of Artificial Insemination (AI )influenced by many factor, there are nutrition, body condition and post thawing motility (PTM). The PTM influenced by liquid N2 storage, equilibration temperature and handling straw. The purpose of this research to compare the effect of thawing duration to frozen semen quality of Limousin and Brahman. This research was done in BIBD, Agriculture Official of Blora, Central Java and Laboratory of Beef Cattle Station Research, Grati. As semen source is bull of Limousin and Brahman with age 2-3 years, body weight + 1200 kg. The data was observed such as: (1) pH, (2) Motility, (3) Live sperm, (4) Abnormality. The research use Randomized Complete Design (RCD) one way there are time of thawing 0, 15, 30, 45 minutes with 10 time repetition. The result of this research showed that the highest motility and live sperm (P<0,05) at the treatment with the duration of thawing 0 minute, there are 41,50% and 66,50% (Limousin frozen semen); 40,00% and 39,58% (Brahman frozen semen). It was concluded that shortening the time of thawing could be repairing the PTM and S/C value. (Animal Production 11(1): 48-52 (2009) Key Words : semen quality, frozen semen, thawing